2017
DOI: 10.1080/10520295.2017.1350750
|View full text |Cite
|
Sign up to set email alerts
|

The role of mast cells and macrophages in amiodarone induced pulmonary fibrosis and the possible attenuating role of atorvastatin

Abstract: Amiodarone (AM) is an effective anti-arrhythmic drug. We investigated the role of mast cells and macrophages on AM induced pulmonary fibrosis and the action of atorvastatin on this fibrosis. Rats were allocated into four groups; negative control (1), positive control (2), 30 mg/kg body weight/day AM (3) and AM + 10 mg/kg/day atorvastatin (4). Lungs were harvested and prepared for histology and immunohistochemistry. Hematoxylin and eosin stained sections of group 3 exhibited disorganized lung architecture. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Not only lysosomes but also cell size (area) was determined because it has been reported that amiodarone increases the number and size of alveolar macrophages in rats [26]. In our study, both CADs at concentrations ≥2.5 µM increased the cell area of M1 macrophages, at ≥5 µM the area of RAW264.7 cells, and at 10 µM the area of THP-1 cells.…”
Section: Effect Of Cads On Cell Areasupporting
confidence: 47%
“…Not only lysosomes but also cell size (area) was determined because it has been reported that amiodarone increases the number and size of alveolar macrophages in rats [26]. In our study, both CADs at concentrations ≥2.5 µM increased the cell area of M1 macrophages, at ≥5 µM the area of RAW264.7 cells, and at 10 µM the area of THP-1 cells.…”
Section: Effect Of Cads On Cell Areasupporting
confidence: 47%
“…An increasing body of evidence has indicated that statins may have a beneficial effect on clinical outcomes in PF and even in COVID‐19 23,36–38 . By searching all the literature investigating the association of statins with PF, including 7 clinical studies 23,24,39–43 and 18 experimental studies, 24,36,44–59 we found that almost all studies trends to indicate that the statins are protective for PF (Supporting information Table S3). It is believed that lipophilic statins are taken up faster by PF lung tissue through passive diffusion than through active uptake 60 .…”
Section: Discussionmentioning
confidence: 92%
“…In another study, researchers found that simvastatin protected the endothelial barrier by inhibiting NOX activity and superoxide production [ 98 ]. El-Mohandes et al found that amiodarone was capable of inducing the generation of degranulated mast cells and alveolar macrophages in alveolar sacs, and the administration of atorvastatin significantly reduced the number of mast cells and alveolar macrophages and inhibited pulmonary fibrosis in rats [ 99 ]. Mast cell granules contain histamine and TGF- β ; following degranulation, the components can promote the proliferation of fibroblasts, and alveolar macrophages can also secrete TGF- β , thereby promoting the enhancement of collagen fiber synthesis and leading to the deposition of ECM [ 100 ].…”
Section: Pathogenesis Of Ipfmentioning
confidence: 99%